Sublethal effect of Abamectin in the functional response of the predator Phytoseiulus persimilis (Athias-Henriot) on Tetranychus urticae (Koch) (Acari: Phytoseiidae, Tetranychidae) - J. I. Monjarás-Barrera; J. C. Chacón-Hernández; E. Cerna-Chávez; Y. M. Ochoa-Fuentes; L. A. Aguirre-Uribe; J. Landeros-Flores (Brazilian Journal of Biology, 2018)
Abstract The biological control used for the control of Tetranychus urticae (Koch) is the predator mite Phytoseiulus persimilis (Athias-Henriot). It is important to the know the effects of acaricides on the biological behavior the Abamectin on the functional response of P. persimilis. The functional response of the predator was of type II exposed to concentration of Abamectin, the functional response parameters: successful attack rate (a’), handling time (Th), search efficiency and the maximum predation theory (T/Th) were affected by the acaricide. The predator spends more time in persecute, dominate, consume and prepair it self to the next searching comparing with the proof subject an the predation ability was affected.